2014
DOI: 10.3389/fncel.2014.00259
|View full text |Cite
|
Sign up to set email alerts
|

In vivo knockdown of Piccolino disrupts presynaptic ribbon morphology in mouse photoreceptor synapses

Abstract: Piccolo is the largest known cytomatrix protein at active zones of chemical synapses. A growing number of studies on conventional chemical synapses assign Piccolo a role in the recruitment and integration of molecules relevant for both endo- and exocytosis of synaptic vesicles, the dynamic assembly of presynaptic F-actin, as well as the proteostasis of presynaptic proteins, yet a direct function in the structural organization of the active zone has not been uncovered in part due to the expression of multiple a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
60
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(60 citation statements)
references
References 47 publications
0
60
0
Order By: Relevance
“…Alternatively, numerous structural proteins have been shown to localize to the ribbon complex (Brandstatter et al, 1999), including Piccolo, Bassoon, Cast/ERC, Rim1, Rim2, but each of these proteins are also found at conventional synapses, which lack the ribbon structure. Of note, a ribbon-specific isoform of Piccolo has been described in retina (Regus-Leidig et al, 2014b, Regus-Leidig et al, 2013), suggesting that ribbon-specific splicing may underlie some of the diversity in ribbon shape and size.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, numerous structural proteins have been shown to localize to the ribbon complex (Brandstatter et al, 1999), including Piccolo, Bassoon, Cast/ERC, Rim1, Rim2, but each of these proteins are also found at conventional synapses, which lack the ribbon structure. Of note, a ribbon-specific isoform of Piccolo has been described in retina (Regus-Leidig et al, 2014b, Regus-Leidig et al, 2013), suggesting that ribbon-specific splicing may underlie some of the diversity in ribbon shape and size.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have begun to unravel the structural and molecular underpinnings of the photoreceptor ribbon synapse (39, 40). In addition to Ribeye (41) and Piccolino (a splice variant of Piccolo) (42), a few molecular components have been associated with precise photoreceptor presynapse morphology and wiring with bipolar cells; these include scaffold protein 4.1G (also called Epb4.1l2), cell adhesion protein ELFN1 (43), and extracellular proteins Pikachurin (44) and auxillary calcium channel subunit α2δ4 (45). Here, we define a set of 26 new molecular determinants that limit the size and/or axonal positioning of the spherule in the appropriate sublamina, two essential features associated with functional specificity of the rod photoreceptor synapse.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Piccolo appears at emerging synapses formed between mossy fiber boutons and cerebellar granule cells as well as between parallel fiber boutons and Purkinje cell dendrites during the earliest stages of cerebellar development (Zhai et al, 2001). The large size of Piccolo and the complexity of the Pclo gene has thwarted most efforts to elucidate its function, though critical roles in retinal ribbon synapse formation and visual function (Regus-Leidig et al, 2014; Muller et al, 2019) as well as the integrity of hippocampal synapses has been identified (Waites et al, 2013). What remains unclear is how Piccolo contributes to cerebellar development and whether, as suggested by genetic studies, it has a primary role in the etiology of PCH3.…”
Section: Introductionmentioning
confidence: 99%